KONSERVASI KURATIF KOLEKSI PERPUSTAKAAN PASCA KEBAKARAN DI DINAS KEARSIPAN DAN PERPUSTAKAAN KABUPATEN PESISIR SELATAN BERBASIS DISASTER PREPAREDNESS IN LIBRARY - Khaerun Nisa; Marlini (ADISAM PUBLISHER, 2024)
The objectives of this research are (1) Describe the condition of the collection post-fire library at the District Archives and Library Service South Coast; (2) Describe the collection's curative conservation activities post-fire library as a recovery stage from the Disaster Preparedness in Libraries at the Coastal District Archives and Library Service South; and (3) Describe the factors that are obstacles the library carries out curative conservation of library collections after the fire at the South Pesisir Regency Archives and Library Service. This research using an approach with the data collection techniques used, namely interviews, observations, and documentation. The subject of this research is the Head Library Sector, Library Management, and Library Staff. As for technique The data analysis used is data collection, data presentation, and drawing conclusions. The research results show that, (1) Condition of library collections post-fire at the Pesisir Selatan Regency Archives and Library Service categorized into 2, namely severely damaged (destroyed) and collection conditions damaged by wetness; (2) Curative conservation activities carried out by the Service archives and libraries of Pesisir Selatan Regency after the fire The condition of collections that are seriously damaged (destroyed) in a library is destruction by throwing it into the landfill. Meanwhile collections Wet printing is done in stages such as drying using a rope and dry using a fan. After all that's done carried out, the collections are arranged into cardboard boxes whose purpose is to Avoid wrinkles and warping of the book. Then arranged neatly inside depot room to keep it safe and protected; and (3) Inhibiting factors the library carries out curative conservation of library collections after the fire in the South Pesisir Regency Archives and Library Service, namely budget, Human Resources, and equipment/facilities for collection repair.